The Influence of Corporate Social Responsibility Programs To The Image of Corporations - Mohammad Hamim Sultoni (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
The social responsibility nowadays is the company’s response to the environmental and social aspects. It is based on the determination of government regulations in Article 74 of Act Number 40 Year 2007 on Limited Liability Companies. The implementation of Corporate Social Responsibility (the so called CSR) program presently is not only as a social responsibility but also as a core of marketing strategy in growing or maintaining the image of the company. Even the results of research conducted by Roper Search Worldwide explained that as much as about 66% of respondents are ready to change brands to the companies that have a positive social image in the form of CSR program. Therefore, this research has an objective to determine the influence of CSR program against the image of the company.This research uses a quantitative approach which has result in a clear and definite conclusion. The findings concluded that the variables of Corporate Social Responsibility (X3) are significantly takes effect and has the most dominant influence with the result t tcount of 4.701 with the significance t of 0.000. Meanwhile, CSR Goals with tcount of 2.552 with significance t of 0.013 have significant influence. While CSR Issue has no significant influence with tcount of -0.411 with significance t of 0.682.